Comparative study between ondansetron vs Palonosetron for controlling postoperative nausea and vomiting - Hasan, Muhammad Masud; Islam, Md Shafiqul; Ara, Anjuman; Fazilatunnesa, -; Rahman, Md Ashiqur; Sultana, Mst Habiba; Akhtar, Sabiha (Community Based Medical Journal, 2017)
Postoperative nausea and vomiting (PONV) is a major complication in patients who undergo surgery under general anaesthesia. Various drug regimens and antiemetic interventions have been tried from time to time for prevention of PONV but with a variable success rate. The aim of the study is to compare between ondansetron vs Palonocstron for controlling postoperative nausea and vomiting. In this prospective study, 100 patients aged 18-60 years of ASA GRADE-I and II scheduled for undergoing surgery under general anaesthesia after taking informed written consent at a tertiary care hospital, were randomly divided into two groups of 50 each. Group-A was given palonosetron 75 μg and Group-B was given ondansetron 4 mg. At 72 hours, nausea and vomiting were statistically significant between ondansetron and palonosetron groups. Postoperative side-effects such as headache, dizziness and drowsiness were not statistically significant between ondansetron and palonosetron groups. In conclusion, the antiemetic efficacy of palonosetron is similar to that of Ondansetron for preventing PONV during the first 24 hours after patients who undergo surgery under general anaesthesia. But after 72 hours, nausea and vomiting were statistically higher in ondansetron group than palonosetron group. CBMJ 2017 July: Vol. 06 No. 02 P: 15-20